(untitled) (Academia Journal of Medicine, 2020)
Background: Hypertension is a leading cause of mortality and morbidity worldwide which doubles the risk of cardiovascular diseases. Hypertension and dyslipidemia are major modifiable risk factors associated with an increasing risk of cardiovascular disease. Aims & Objective: To study the different components of lipid profile in newly detected adult hypertensive patients and to compare the lipid profile changes among newly detected adult hypertensive patients with normotensive patients in a tertiary care hospital .Subjects and Methods: The study was done in the department of General medicine in Hassan institute of medical sciences, Hassan, Karnataka a tertiary care hospital. Patients were selected randomly from outpatient and in patients departments after taking consent and fulfilling the inclusion and exclusion criteria. Two hundred and fifteen age and sex matched patients were enrolled for the study and they were divided into two groups based on blood pressure. Group A - study group (109) newly detected hypertension patients and Group B –control group (106) comprising normotensive patients. Both the groups fasting lipid profile was studied and compared. Results: Total 215 patients were included in the study, of which 109 patients were in group A (study group) comprising newly detected hypertension patients and 106 patients were in group B(control) comprising of normotensive patients. The mean SBP (systolic blood pressure) was 159.4 mm of Hg in Group A whereas it was 113.2 in Group B, the mean DBP (diastolic blood pressure) was 99.4mm of Hg in Hypertensive patients (Group A), and it was 73.1 in normotensive patients (Group B). Serum levels of cholesterol, triglyceride and LDL were 194.2, 152.2 and 122.2 mg/dl respectively in hypertensive patients, whereas in normotensive patients they were 146.4, 110.2 and 102.6 mg/dl respectively which were higher in hypertensive patients. Whereas serum HDL was almost the same in both the groups. Conclusion: Newly detected adult hypertensive patients are dyslipidemic as compared to normotensive patients, so proper blood pressure control and monitoring of lipid profile at regular intervals helps in preventing major complications such as cardiovascular diseases and cerebrovascular accidents.